Spatial analysis of environmental factors influencing typhoid endemicity in Kelantan, Malaysia - Shamsul Azhar Shah,; Hiroshi Suzuki,; Mohd Rohaizat Hassan,; Reiko Saito,; Nazarudin Safian,; Shaharudin Idrus, (Universiti Kebangsaan Malaysia, 2012)
The determination of the high-risk area and clusters of typhoid cases is critical in typhoid control. The purpose of this study was to identify and describe the epidemiology and spatial distribution of typhoid in four selected districts in Kelantan using GIS (geographical information system). A total of 1215 (99%) of the cases were coordinated with GPS (global positioning system) and mapping was done using ArcGIS 9.2. Spatial analysis was performed to determine the cluster and high-risk area of typhoid. Results showed that typhoid incidence was not associated with race and sex. Most affected were from the age group of 5-14 followed by 15-24 year olds. Nine sub-districts were categorized as highly endemic. In addition typhoid has shown a significant tendency to cluster and a total of 22 hotspots were found in Kota Bharu, Bachok and Tumpat with a few sub districts identified as high risk for typhoid. No significant relationships between the treated water ratio and flood risk area were found with the cluster of cases. The cluster of typhoid cases in the endemic area did not appear to be related to environmental risk factors. Understanding the characteristics of these clusters would enable the prevention of typhoid disease in the future.